Enhanced hydrogen storage properties of MgH2 through doping with titanium-based catalyst materials: A review and bibliometric analysis - Saeid, Mohammed Faraj; Abdulkadir, B. A.; Mohammad Ismail, .; Herma Dina, Setiabudi (Elsevier Ltd, 2025)
The quest for effective and reversible hydrogen storage remains a central issue in the advancement of hydrogen energy systems. Among candidate materials, magnesium hydride (MgH2) stands out due to its high hydrogen capacity and abundance. Nevertheless, its real application is severely limited by slow hydrogenation/dehydrogenation kinetics and high thermodynamic stability, a critical bottleneck for onboard and stationary storage technologies. This review specifically addresses this challenge by exploring the novel role of titanium-based (Ti-based) catalyst materials in overcoming these limitations. This study provides a comprehensive and up-to-date review of recent developments in Ti-based catalyst doping for MgH2, focusing on how such doping alters the sorption mechanisms at both macroscopic and atomic levels. It covers various synthesis methods used to incorporate Ti-based additives, highlighting their influence on catalyst dispersion, particle size, and interfacial structure. Distinctions between physisorption and chemisorption processes are drawn, followed by an in-depth examination of nanostructured Ti catalysts, including Ti hydrides, oxides, intermetallics, and transition metal carbides and nitrides (MXenes), and their roles in lowering activation energy, enhancing hydrogen diffusion, and improving the thermodynamic properties by reducing the enthalpy and destabilizing Mg–H bonds. The novel contribution of this review lies in its synthesis of current knowledge with a focus on interfacial interactions and atomic-level mechanisms, as revealed by advanced characterization techniques and computational models. Additionally, a bibliometric analysis is presented to map the evolution of research in this field, identify key contributors, and uncover emerging trends and hotspots. By coupling materials science insights with bibliometric intelligence, this review outlines critical gaps and future directions, supporting the rational design of Ti-MgH2 composites for real-world hydrogen storage applications.